Strategi Komunikasi Pemasaran Sanggar Musik Gita Loka (SMGL) - Maghfuroh, Mazkiyah; Zulaikha, Zulaikha; Maella, Nur Annafi Farni Syam (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research is to analyze the marketing communications strategy of Sanggar Musik Gita Loka (SMGL) in attracting the interest of prospective new students as well as awareness, using the SOSTAC analysis method modeled by Paul R. Smith (2022) with a descriptive qualitative approach. The results of the research show that the use of social media Instagram and Facebook at Sanggar Musik Gita Loka was successful in attracting the interest of prospective new students as well as awareness, although the percentage was not as high as conventional promotional tools. The results of this research reveal that overall Sanggar Musik Gita Loka (SMGL)' has succeeded in implementing the SOSTAC strategy in attracting prospective new students even though it has not yet 100% met the target.